Around the world in 80 days - Verne, Jules; Goldstein, David Andrew; Verne, Jules, 1828-1905.; Walt Disney Pictures; Walden Media (New York : Hyperion Books for Children, 2004)
Inventor Phileas Fogg bets members of his London gentlemen's club that he can travel around the world in eighty days and agrees to stop inventing if he fails. He is accompanied by Passepartout, a Chinese thief who steals a valuable jade Buddha and then takes refuge with Fogg. Includes fact pages that explains some of the changes made in Jules Verne's novel and important people, places and things featured in Verne's novel and this adaptation.
Ages 8-10.
Keywords: Voyages around the world -- Fiction. -- General books; Adventure and adventurers -- Fiction; Voyages around the world -- Juvenile fiction; Film adaptations; Adventure fiction; Movie novels